The Role of Stress of Covid-19 Infection during Work Shifts, and Nurses' Emotional Exhaustion Under Covid-19 Conditions - Farshid Aslani; Akbar Bahmani (Shiraz University of Medical Sciences, 2022)
Background: The sudden outbreak of the novel coronavirus has caused a waveof concern throughout society and among medical staff members. Consecutivepeaks, persistent stress, along with disorders caused by work shifts lead to physicalweakness and psychological complications over time. the aim of the presentstudy was to investigate the effect of work shifts under Covid-19 conditions onthe emotional exhaustion of medical staff members with the mediating role ofstress of Covid-19 infection.Methods: This applied and descriptive field research was conducted crosssectionallyin 2020. The statistical population included 250 nurses fromImam Khomeini Hospital in Amol city, Iran. A total of 150 individuals wereselected using Morgan Table and simple random sampling methods. Astandard questionnaire with confirmed validity and reliability was used as thedata collection instrument. To perform data analysis, the structural equationmodeling method was used to measure the fit of the research model and test thehypotheses in SPSS ver. 22 and Amos ver. 22 software.Results: The results showed that disorders caused by work shifts had a significanteffect on the emotional exhaustion and stress of Covid-19 infection in nurses ona medical staff. Stress of Covid-19 infection had a significant effect on nurses'emotional fatigue. The mediating role of stress of Covid-19 infection in therelationship between work shifts and emotional exhaustion was also confirmed.Conclusion: The transmission rates of different types of Covid-19 mutationswith consecutive peaks have caused constant stress in nurses. Related disorderscaused by work shifts and the large number of patients and hospitalizations willlead to a lack of energy and of concentration in nurses, which in turn will leadto poor performance, reduced quality of life, and ultimately emotional fatigue.